A systematic review with meta-analysis of the effects of arm exercise training programs on arteriovenous fistula maturation among people with chronic kidney disease - Sothida Nantakool (2020)
© 2020 International Society for Hemodialysis This study systematically reviewed the evidence and quantified the effectiveness of arm exercise training programs, before and after arteriovenous fistula (AVF) operation on AVF maturation, among people with chronic kidney disease. Scopus, CINAHL, PubMed, Science Direct, Cochrane Library, and reference lists were searched. Experimental studies that investigated the effect of arm exercise before and post-operation on AVF maturations were included. Screened and extracted data were administered by two independent reviewers. Seven studies with preoperative exercise were included in a systematic review, while five studies were analyzed in a meta-analysis. Preoperative exercise significantly increased vessel diameters and grip strength after training. Postoperative exercise had higher clinical and ultrasonographic (US) maturation rates and arterial blood flow than controls (risk ratio [RR], 1.44; 95% confidence interval [CI], 1.23–1.69; RR, 1.27; 95% CI, 1.02–1.57; weight mean difference, 166.03; 95% CI, 27.58–304.49, respectively). Subgroup analysis showed that isometric exercise training promoted clinical and US maturations (RR, 2.40; 95% CI, 1.51–3.82; RR, 1.53; 95% CI, 1.02–2.30, respectively), whereas isotonic exercise promoted clinical maturation (RR, 1.18; 95% CI, 1.03–1.34). Grip strength had a greater trend in the intervention group than controls (standardized mean difference, 0.59; 95% CI, −0.06 to 1.25). In conclusion, arm exercise training improves vascular function, which is essential before surgery. The meta-analysis suggested that arm exercise training promotes AVF clinical and US maturations after surgery. Subgroup analysis suggested that isometric-arm exercise training may have a larger effect on AVF maturation. However, more studies are needed to draw a solid conclusion.